Identification of design variables and criterion variables towards the integration of user requirements into preliminary design. (9th April 2007) - Dore, Raphaelle; Pailhes, Jerome; Fischer, Xavier; Nadeau, Jean-Pierre
Industrial designers have to design products that meet User Requirements. User Requirements are usually used as validation elements at the end of the Product Design process. Yet, at this stage in the Product Design process, many decisions have already been made. Decisions made by Designers in the Preliminary Design phase account for 70% of total product development costs. Therefore, iterating a Design Process is very expensive. The object of the present approach is to integrate User Requirements at the beginning of Preliminary Design, using functional specifications. The general object of the present approach is to find links between a Sensory Characterisation and a Functional Characterisation of a product. Using such links, Designers will be able to evaluate the influence of design decisions on User sensations. User requirements can play a major role as physical or financial aspects in Preliminary Design.